EFEKTIVITAS MODEL PROBLEM BASED LEARNING BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK KELAS IV PADA MATA PELAJARAN IPAS DI SD NEGERI KLECO 1 SURAKARTA TAHUN PELAJARAN 2025/2026 - Ramadhani Argamawan; Elinda Rizkasari; Sarafuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The primary focus of this study is to measure the level of effectiveness in sharpening the critical thinking skills of fourth-grade students at SD Negeri Kleco 1 Surakarta in the Natural and Social Sciences (IPAS) subject (academic year 2025/2026) through the implementation of a Problem-Based Learning (PBL) model integrated with local wisdom. A quantitative method using a Pre-Experimental design (One Group Pretest-Posttest) was applied to 28 students of class IV B (with an equal composition of 14 boys and 14 girls) at the school. The sample was selected using the Cluster Random Sampling procedure, while the field data collection took place from May 19 to 21, 2026. Data gathered through tests, observations, and documentation techniques were subsequently analyzed using the Shapiro-Wilk prerequisite test, the paired sample t-test comparative analysis, and the N-Gain index calculation. Based on the data analysis results, there was a sharp increase in the students' average achievement, rising from 56.54 in the pretest to 80.11 in the posttest. The paired sample t-test results revealed a value of t-count = -15.489 with a significance of 0.000 (p < 0.05), meaning that the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. According to the average N-Gain score of 0.56, the efficacy of this instructional model is categorized under the "fairly effective" criterion. Consequently, it is empirically concluded that integrating local wisdom into the PBL scheme can optimize the critical thinking abilities of fourth-grade students at SD Negeri Kleco 1 Surakarta in the IPAS subject for the 2025/2026 academic year.